Arylvinylpiperazine Amides, a New Class of Potent Inhibitors Targeting QcrB of Mycobacterium tuberculosis - Caroline S. Foo (American Society for Microbiology, 2018)
ABSTRACT New drugs are needed to control the current tuberculosis (TB) pandemic caused by infection with Mycobacterium tuberculosis. We report here on our work with AX-35, an arylvinylpiperazine amide, and four related analogs, which are potent antitubercular agents in vitro. All five compounds showed good activity against M. tuberculosis in vitro and in infected THP-1 macrophages, while displaying only mild cytotoxicity. Isolation and characterization of M. tuberculosis-resistant mutants to the arylvinylpiperazine amide derivative AX-35 revealed mutations in the qcrB gene encoding a subunit of cytochrome bc1 oxidase, one of two terminal oxidases of the electron transport chain. Cross-resistance studies, allelic exchange, transcriptomic analyses, and bioenergetic flux assays provided conclusive evidence that the cytochrome bc1-aa3 is the target of AX-35, although the compound appears to interact differently with the quinol binding pocket compared to previous QcrB inhibitors. The transcriptomic and bioenergetic profiles of M. tuberculosis treated with AX-35 were similar to those generated by other cytochrome bc1 oxidase inhibitors, including the compensatory role of the alternate terminal oxidase cytochrome bd in respiratory adaptation. In the absence of cytochrome bd oxidase, AX-35 was bactericidal against M. tuberculosis. Finally, AX-35 and its analogs were active in an acute mouse model of TB infection, with two analogs displaying improved activity over the parent compound. Our findings will guide future lead optimization to produce a drug candidate for the treatment of TB and other mycobacterial diseases, including Buruli ulcer and leprosy. IMPORTANCE New drugs against Mycobacterium tuberculosis are urgently needed to deal with the current global TB pandemic. We report here on the discovery of a series of arylvinylpiperazine amides (AX-35 to AX-39) that represent a promising new family of compounds with potent in vitro and in vivo activities against M. tuberculosis. AX compounds target the QcrB subunit of the cytochrome bc1 terminal oxidase with a different mode of interaction compared to those of known QcrB inhibitors. This study provides the first multifaceted validation of QcrB inhibition by recombineering-mediated allelic exchange, gene expression profiling, and bioenergetic flux studies. It also provides further evidence for the compensatory role of cytochrome bd oxidase upon QcrB inhibition. In the absence of cytochrome bd oxidase, AX compounds are bactericidal, an encouraging property for future antimycobacterial drug development.